2014
DOI: 10.4238/2014.march.24.13
|View full text |Cite
|
Sign up to set email alerts
|

A genetic linkage study in Brazil identifies a new locus for persistent developmental stuttering on chromosome 10

Abstract: ABSTRACT. Although twin, adoption, and family studies demonstrate that genetic factors are involved in the origins of stuttering, the mode of transmission of the disorder in families is not well defined and stuttering is considered a genetically complex trait. We performed a genomewide linkage scan in a group of 43 Brazilian families, each containing multiple cases of persistent developmental stuttering. Linkage analysis under a dominant model of inheritance generated significant evidence of linkage in two Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Other authors described association in additional chromosomal regions [71][72][73] . Using high density genotyping, SLC6A3 and DRD2 were identified as other candidate genes in the Chinese Han population [74] .…”
Section: Stutteringmentioning
confidence: 95%
“…Other authors described association in additional chromosomal regions [71][72][73] . Using high density genotyping, SLC6A3 and DRD2 were identified as other candidate genes in the Chinese Han population [74] .…”
Section: Stutteringmentioning
confidence: 95%
“…Highly significant Domingues et al (2014) 10q Significant members of four of the 44 Pakistani families originally included in the genome-wide linkage search. This suggested that the GNPTAB p.Glu1200Lys mutation, which was subsequently shown to be a founder mutation (Fedyna et al 2011), underlies the disorder in~9% of Pakistani families with multiple cases of persistent stuttering.…”
Section: Gnptabmentioning
confidence: 99%
“…Linkage studies for persistent stuttering (see Table 1) conducted in several different populations have implicated multiple genomic loci and different modes of inheritance Raza et al 2012Raza et al , 2013Domingues et al 2014). A linkage study in a large consanguineous Pakistani family led to the identification of a linkage peak on chromosome 12 (Kang et al 2010).…”
Section: Stutteringmentioning
confidence: 99%